Performance of albumin-bilirubin score in prediction of hepatic encephalopathy in cirrhotic patients with acute variceal bleeding - Rehab Elsayed Elsafty; Abdallah Ahmed Elsawy; Ahmed Fawzy Selim; Atef Mohamed Taha (Egyptian Liver Journal, 2021)
Abstract Background Hepatic encephalopathy exacerbates the morbidity, delays hospital discharge, and increases the rate of readmissions of cirrhotic patients, particularly those are admitted by acute variceal bleeding. We evaluated the performance of albumin-bilirubin score in prediction of hepatic encephalopathy in cirrhotic patients with acute variceal bleeding, in comparison to Child-Pugh and MELD scores. This prospective cohort study was conducted on 250 cirrhotic patients who were consecutively presented by acute variceal bleeding in the period from January to December 2020 at Tanta university emergency hospital. Albumin-bilirubin, Child-Pugh, and MELD scores were measured at admission, and then all patients were followed up for 4 weeks after endoscopic bleeding control for possible occurrence of hepatic encephalopathy Results Albumin-bilirubin, Child-Pugh, and MELD scores had significant performances in prediction of hepatic encephalopathy in cirrhotic patients with acute variceal bleeding; in this regard, albumin-bilirubin score had the highest accuracy (AUC 0.858, CI 0.802-0.914, sig 0.000) followed by Child-Pugh score (AUC 0.654, CI 0.574–0.735, sig 0.001) and then MELD score (AUC 0.602, CI 0.519–0.686, sig 0.031). The cumulative incidence of hepatic encephalopathy in cirrhotic patients with albumin-bilirubin grade 3 was found to be significantly more than that present in albumin-bilirubin grade 2; most of these hepatic encephalopathy cases occurred in the first 2 weeks of follow-up period. Conclusions Albumin-bilirubin score has a significant performance in risk prediction of hepatic encephalopathy in cirrhotic patients with acute variceal bleeding better than Child-Pugh and MELD scores. Albumin-bilirubin grades could be used as a risk stratifying tool to triage cirrhotic patients who will benefit from early discharge after bleeding control and those patients who will benefit from prophylactic measures for hepatic encephalopathy.